1997
DOI: 10.1007/bf02725502
|View full text |Cite
|
Sign up to set email alerts
|

Deafness and its prevention—Indian scenario

Abstract: Auditory sense is crucial for the mental development of a child and for the human abilities and social adaptation subsequently in life. Unfortunately, for various reasons the deafness has not drawn enough attention. There have been many studies in India on etiology and prevalence on regional basis. Rural population has been shown to be affected more often than the urban population. Poor economic background has also been held partially responsible. The lack of health awareness and education has played a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
12
1
1
Order By: Relevance
“…An estimated 80 million people in the country have significant HL, 35 million of whom are younger than 14 years (12). Comprehensive information on the causes of HL in India is lacking, but it has been reported Local beliefs and community attitudes play a predominant role in the success of immunization programs (31) No supported infant screening programs in place; G60% of patients that do undergo screening return for follow-up (32) (Continued on next page) that the most common preventable cause of profound HL is congenital rubella, with estimates ranging from approximately 30 (38) Overall, the prevalence of HL is greater in rural than in urban areas (12). In 1 study, the prevalence of HL was found to be significantly associated with economic status (13).…”
Section: Asiamentioning
confidence: 99%
“…An estimated 80 million people in the country have significant HL, 35 million of whom are younger than 14 years (12). Comprehensive information on the causes of HL in India is lacking, but it has been reported Local beliefs and community attitudes play a predominant role in the success of immunization programs (31) No supported infant screening programs in place; G60% of patients that do undergo screening return for follow-up (32) (Continued on next page) that the most common preventable cause of profound HL is congenital rubella, with estimates ranging from approximately 30 (38) Overall, the prevalence of HL is greater in rural than in urban areas (12). In 1 study, the prevalence of HL was found to be significantly associated with economic status (13).…”
Section: Asiamentioning
confidence: 99%
“…Scanty school surveys are available from both rural and urban setup and demonstrate prevalence of 6.3% of cases in the urban group and 32.8% in the rural group (12).…”
Section: Deafnessmentioning
confidence: 99%
“…Poverty, ignorance, poor hygiene, inadequate medical guidance, and customs and beliefs based on tradition and culture are reported to be reasons for poor health awareness (Kumar, 1997). Having appropriate health-related information ensures that people are better equipped to access services (WHO, 2010).…”
Section: Introductionmentioning
confidence: 99%